Escaping North Korea: Defiance and Hope in the World's Most Repressive Country - Kim, Mike (Rowman & Littlefield Publishers, 2008)
The first of its kind, this book provides a unique inside look into the hidden world of ordinary North Koreans. Mike Kim, who worked with refugees on the Chinese border for four years, recounts their experiences of enduring famine, sex-trafficking, and torture, as well as the inspirational stories of those who overcame tremendous adversity to escape the repressive regime of their homeland and make new lives. One of the few Americans granted entry into the secretive "Hermit Kingdom," Kim came to know the isolated country and its people intimately. His North Korean friends entrusted their secrets to him as they revealed the government's brainwashing tactics and confessed their true thoughts about the repressive regime that so rigidly controls their lives. Civilians and soldiers alike spoke of what North Koreans think of Americans and war with America. Children remembered the suffering they endured through the famine. Women and girls recalled their horrific experiences at the hands of sex-traffickers. Former political prisoners shared their memories of beatings, torture, and executions in the gulags. With the permission of these courageous individuals, Kim now shares their stories and recounts his dramatic experiences leading North Koreans to asylum through the six-thousand-mile modern-day underground railway through Asia. His unflinching narrative exposes the truth about North Korea, stripping away the last veils that still shroud this brutal dictatorship.